PEMANFAATAN GIBERELIN UNTUK MEMACU PERTUMBUHAN DAN PRODUKSI MELON MENGGUNAKAN HIDROPONIK SISTEM SUMBU - M. I. Jazuli; Siti Nurul Aini; N. S. Khodijah (JURNAL BIOINDUSTRI (JOURNAL OF BIOINDUSTRY), 2021)
Melon production has decrease due to decreasing agriculture land area. An effort to increases melon production can be done by cultivating melons using a hydroponic system. Gibberellins can be used to increase melon production in Bangka Belitung. This research  aims to determine the effect and  gibberellin doses that has increase melon growth and production which cultivated using hydroponic wick system. This research was conducted from January to April 2020 at the Research and Experimental Station, Faculty of Agriculture, Fisheries and Biology, Universitas Bangka Belitung. The experimental design used in this study was a single completely randomized design (CRD) with various gibberellin concentrations (0 ppm, 20 ppm, 40 ppm, 60 ppm, 80 ppm, 100 ppm). Gibberellin was applied by giving it at the soaking seeds period and by spraying it onto the leaves of the plants. The results of study showed that the application of gibberellin (GA3) had a significant effect on stem diameter, leaf area, fruit weight, fruit diameter, pulp thickness and total plant dissolved solids. The application of gibberellin with 100 ppm concentration is the best treatment to increasing growth and 80 ppm concentration is the best treatment to increasing yield of melon with wick hydroponic cultivation system.